Prenatal Prediction of Poor Maternal and Offspring Outcomes: Implications for Selection into Intensive Parent Support Programs - Chittleborough, Catherine R. (Springer US, 2011)
This study examined the predictive ability of mother’s age, antenatal depression, education, financial difficulties, partner status, and smoking for a range of poor maternal and offspring outcomes assessed up to 61 months postnatally. Outcomes obtained from the Avon Longitudinal Study of Parents and Children (ALSPAC) were maternal postnatal depression at 8 weeks (n = 10,070), never breastfeeding (n = 7,976), feelings of poor attachment (n = 8,253) and hostility (n = 8,159) at 47 months, and not in employment, education or training (NEET, n = 8,265) at 61 months. Only a small proportion of women with each outcome were aged less than 20 years when they were pregnant. At least half of the women experiencing these outcomes, and up to 74.7% of women with postnatal depression, could be identified if they had at least one of the predictors measured during pregnancy (age < 20, depression, education less than O level, financial difficulties, no partner, or smoking). Model discrimination was poor using maternal age only (area under the receiver operator characteristic (AUROC) curve approximately 0.52), except for never breastfeeding (0.63). Discrimination improved (AUROC: 0.80, 0.69, 0.62, 0.60, 0.66 for depression, never breastfeeding, poor attachment, hostility and NEET, respectively) when all six predictors were included in the model. Calibration improved for all outcomes with the model including all six predictors, except never breastfeeding where even age alone demonstrated good calibration. Factors other than young maternal age, including education, smoking and depression during pregnancy should be considered in identifying women and their offspring likely to benefit from parenting support interventions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10995-011-0818-5) contains supplementary material, which is available to authorized users.